Penerapan Model Kooperatif Tipe NHT untuk Meningkatkan Hasil Belajar Matematika Pada Siswa SMP Negeri 5 Kota Ternate - Awal, Yani (Peneliti.net, 2023)
The aim of this study is to determine the improvement of learning outcomes through the implementation of the Numbered Heads Together (NHT) cooperative model on students at SMP Negeri 5 Kota Ternate. To achieve this objective, the researcher employed a classroom action research approach, which involved planning, implementation, observation, and reflection in each cycle. The subjects were seventh-grade students at SMP Negeri 5 Kota Ternate. Data collection techniques included observation, tests, and documents. Both quantitative and qualitative analyses were conducted. Quantitative analysis involved calculating average scores and classical completeness. Qualitative analysis depicted teacher and student activities, as well as learning outcomes in detailed and comprehensible sentences. The results of the first cycle showed a significant improvement. Out of 27 students, 78% achieved lesson completion with an average score of 80.58, an increase from the initial cycle test. Classical completeness reached 77.78%. In the second cycle, test results indicated positive achievements in mathematics learning. Out of 27 students, 96% successfully achieved learning completeness with an average score of 69.04. This suggests that the learning model and improvement strategies effectively enhanced understanding and academic performance for seventh-grade students at SMP Negeri 5 Kota Ternate